'The problem is the silence': challenges providing support to local INGO staff in Gaza. Issue 1 (March 2016) - Gilbert, Jane
Abstract : This field report reviews some of the challenges encountered in providing support to local international, nongovernmental organisations staff in Gaza, shortly following the cessation of conflict in July and August of 2014. Methodology and the content of group sessions are described. The paper concludes with highlights from the evaluation, reflections on what was learned, and some recommendations on the provision of further staff support in the future.